IPO performances of VC-backed & non-backed companies: a cross country comparison of Germany & the UK - Özgüneş, Kadri. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
The significance of the venture capitalist̕s existence in the shareholders̕ structure ofan issuing company has attracted several academic researchers̕ attention. Presumingthat the Certification Theory holds, it is expected that underpricing of VC backed companies are significantly lower than that of non-VC backed companies. In order toinvestigate this phenomenon we use 374 German and 274 British IPO data for theperiod of 1998-2005. The OLS results of the study exhibit that, although thedynamics of the markets are quite different from each other, the Certification Theory holds in both of these financial markets. Another important outcome of the study isas companies approached to their lock up expiration date, price performances of VCbacked companies are statistically significantly lower than the price performances ofnon-VC backed companies. This outcome is true for Germany but not statistically true for the UK. The study also shows that contrary to general belief, when there isan Agency Effect within an IPO (i.e. a relationship between the underwriter and theventure capitalist in the issued company), underpricing of such company is slightly(but not statistically significantly) lower than an issue with no agency effect. This result may be considered the indication of the strength of the certification effects ofventure capitalists and underwriters in these markets.
Keywords: Going public (Securities) -- Germany.; Going public(Securities) -- Great Britain.